2006
DOI: 10.1586/17446651.1.6.783
|View full text |Cite
|
Sign up to set email alerts
|

Stress and the neuroendocrine system: the role of exercise as a stressor and modifier of stress

Abstract: In this article, the physiological impact of one form of stress -physical exercise -on the neuroendocrine system will be discussed. The specific intent of the review is to present an overview of stress endocrinology, the conceptual models associated with this area of study, and a discourse on the dual role of exercise as both a stressor and a modifier of stress within the neuroendocrine system. These points are addressed with respect to the current research literature dealing with exercise endocrinology in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
156
1
18

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(179 citation statements)
references
References 46 publications
4
156
1
18
Order By: Relevance
“…Certain mental health conditions are associated with high anxiety levels (eg, posttraumatic stress disorder), which can lead to enhanced sympathetic nervous system and hypothalamic-pituitary-adrenal axis activity. [34][35][36] Subsequently, resting levels of circulating catecholamines, adrenocorticotropic hormone, b-endorphin, and cortisol also may be elevated in these conditions. In contrast, persons who are depressed may have low arousal levels and suppressed levels of the aforementioned hormones.…”
Section: Biologic Factorsmentioning
confidence: 99%
“…Certain mental health conditions are associated with high anxiety levels (eg, posttraumatic stress disorder), which can lead to enhanced sympathetic nervous system and hypothalamic-pituitary-adrenal axis activity. [34][35][36] Subsequently, resting levels of circulating catecholamines, adrenocorticotropic hormone, b-endorphin, and cortisol also may be elevated in these conditions. In contrast, persons who are depressed may have low arousal levels and suppressed levels of the aforementioned hormones.…”
Section: Biologic Factorsmentioning
confidence: 99%
“…Physical exercise, as a powerful stressor with physical, psychological, and physiological effects, is proposed to have a modifying role on the circulating levels of cortisol [44,45]. Studies have shown that moderate to high intensity exercise increases circulating levels of cortisol, while low intensity exercise may even result in reduced cortisol levels [46].…”
Section: Discussionmentioning
confidence: 99%
“…Upon released into the blood, cortisol acts on a variety of peripheral tissues, such as skeletal muscle, adipose tissue, and the liver. In the adipose tissues, it induces the hydrolysis of triglycerides into free fatty acids and glycerol (Hackney, 2006, McMurray & Hackney, 2000, Viru & Viru, 2004. It has been found that cortisol increases glycogen breakdown in the liver (Kalamidas & Kotoulas, 2000).…”
Section: Discussionmentioning
confidence: 99%